Government-to-business: the Brazilian Public Digital Bookkeeping System (Sped) and the eSocial Project - Ramos Junior, Helio Santiago (2014)
This paper presents some initiatives of government-to-business in Brazil: The Sped and its project called eSocial. The Sped Fiscal is the Brazilian Public Digital Bookkeeping System and it can be considered an innovation in the relation between the government and the corporate taxpayers, especially in the informatization area. In this research, we explain how it works and its regulatory legislation. After that, we show some benefits of this system. The eSocial Project is the Digital Bookkeeping System of Tax, Social Security and Labor Obligations which is integrated to the Sped Fiscal system. So we make comments about both projects in order to present these new features which have been in development in Brazil.